2016
DOI: 10.1038/srep33677
|View full text |Cite
|
Sign up to set email alerts
|

Ramipril attenuates left ventricular remodeling by regulating the expression of activin A-follistatin in a rat model of heart failure

Abstract: Prior studies have shown that overexpression of ACT A can lead to ventricular remodeling in rat models of heart failure. Furthermore, recently work studying demonstrated that stimulation of activin An expression in rat aortic smooth muscle (RASM) cells by angiotensin II (Ang II). Ramipril is a recently developed angiotensin converting enzyme (ACE) inhibitor. To investigate the effects of Ramipril on expression of ACT A-FS, we established the rat model of heart failure after myocardial infarction (MI), and divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The improved skin parameters were associated with the downregulated phosphorylation of SMAD2/3 and TAK1, which indicated the inhibition of both the canonical and noncanonical TGF-β1 pathways. Our results are consistent with previous reports on the effects of the RAS on myocardial infarction, which demonstrate the efficacy of ramipril in reducing fibrosis and collagen accumulation 31 , 32 . Our results also suggest that the beneficial effects of the RAS blockade induced by ACEI probably also extend to ARBs, such as losartan.…”
Section: Discussionsupporting
confidence: 93%
“…The improved skin parameters were associated with the downregulated phosphorylation of SMAD2/3 and TAK1, which indicated the inhibition of both the canonical and noncanonical TGF-β1 pathways. Our results are consistent with previous reports on the effects of the RAS on myocardial infarction, which demonstrate the efficacy of ramipril in reducing fibrosis and collagen accumulation 31 , 32 . Our results also suggest that the beneficial effects of the RAS blockade induced by ACEI probably also extend to ARBs, such as losartan.…”
Section: Discussionsupporting
confidence: 93%
“…12,31 Specifically, it has been shown that overexpression of activin A leads to ventricular remodelling in rat models of heart failure. 33 Besides these effects, activin A has been described as an additional factor contributing to diabetic cardiomyopathy. 32 Recent research has also demonstrated that the secretome from human epicardial (but not subcutaneous) adipose tissue can induce myocardial fibrosis and that the adipo-fibrokine activin A constitutes an important mediator of this profibrotic effect, which can be neutralized by an anti-activin A antibody.…”
Section: Discussionmentioning
confidence: 99%
“…7 Interestingly, further findings have suggested that the angiotensin-converting enzyme inhibitor Ramipril benefited LV remodelling by reducing fibrosis and collagen accumulation in the left ventricle of rats after myocardial infarction, an observation which was also associated with down-regulation of activin A expression. 33 Besides these effects, activin A has been described as an additional factor contributing to diabetic cardiomyopathy. 14,23 Activin A released from epicardial adipose tissue of obese type 2 diabetic patients provoked impairment of myocardial contractility by reduction of sarcomer shortening, cytosolic calcium flow and expression of sarco/endoplasmic reticulum Ca 2+ ATPase and decreased insulin-mediated glucose uptake in atrial rat cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…As the cornerstone of clinical treatment of heart failure, angiotensin-converting enzyme inhibitors (ACEIs) improve ventricular remodeling (Wei et al, 2016). However, whether ACEIs improve ventricular remodeling in rabbits with ischemic heart failure in association with Gal-3 downregulation remains unclear.…”
Section: Introductionmentioning
confidence: 99%